Self-Control and Emotion Regulation Mediate the Impact of Karate Training on Satisfaction With Life - Potoczny, Wiktor; Herzog-Krzywoszanska, Radoslawa; Krzywoszanski, Lukasz (Frontiers in Behavioral Neuroscience, 2022)
Physical activity is an important determinant of a healthy lifestyle. Regular participation in sports-related activities contributes to the maintenance of good psychophysiological and social health. Long-term physical activity has a positive impact on subjective well-being and can reduce stress. Karate is a specific physical activity which focuses on self-regulation and self-development; therefore, it may reduce impulsivity and improve self-control. Good self-control is also related to satisfaction with life and well-being. The presented study aimed to examine the possible intermediate impact of self-control and emotion regulation on the relationship between karate training and satisfaction with life. Fifty-eight karate practitioners and fifty-nine control subjects participated in the research. The Satisfaction With Life Scale and the Brief Self-Control Scale were applied in order to assess life satisfaction and the general level of self-control. The Emotion Regulation Questionnaire was used to assess suppression and reappraisal, both of which are distinct aspects of emotion regulation. The direct and indirect relationships between karate training and satisfaction with life were investigated using a linear regression model that included self-control, suppression and reappraisal as mediating variables. No direct effects of karate training on satisfaction with life were found, whereas karate training was indirectly associated with satisfaction with life via the indirect path that leads through self-control and reappraisal. This indicates that self-control and reappraisal fully mediate the impact of karate training on subjective well-being. Karate training can therefore play an important role in shaping volitional and personality characteristics, both of which contribute to increasing the well-being of trainees.